Benefits of combined exercise training on arterial stiffness and blood pressure in spontaneously hypertensive rats treated or not with dexamethasone - Tardelli, Lidieli P.; Duchatsch, Francine; Herrera, Naiara A.; Ruiz, Thalles Fernando R.; Pagan, Luana U.; Vicentini, Carlos A.; Okoshi, Katashi; Amaral, Sandra L. (Frontiers in Physiology, 2022)
Dexamethasone (DEX)-induced arterial stiffness is an important side-effect, associated with hypertension and future cardiovascular events, which can be counteracted by exercise training. The aim of this study was to evaluate the mechanisms induced by combined training to attenuate arterial stiffness and hypertension in spontaneously hypertensive rats treated or not with dexamethasone. Spontaneously hypertensive rats (SHR) underwent combined training for 74 days and were treated with dexamethasone (50µg / kg s.c.) or saline solution during the last 14 days. Wistar rats were used as controls. Echocardiographic parameters, blood pressure (BP) and pulse wave velocity (PWV), as well as histological analyses of the heart and aorta, carotid and femoral arteries were performed. At the beginning, SHR had higher BP and PWV compared with Wistar rats. After 60 days, while BP increased in sedentary SHR, combined exercise training decreased BP and PWV. After 74d, the higher BP and PWV of sedentary SHR was accompanied by autonomic imbalance to the heart, cardiac remodeling, and higher arterial collagen deposition. DEX treatment did not change these parameters. On the other hand, trained SHR had reduced BP and PWV, which was associated with better autonomic balance to the heart, reduced myocardial collagen deposition, as well as lower arterial collagen deposition. The results of this study suggest that combined training, through the reduction of aortic collagen deposition, is an important strategy to reduce arterial stiffness in spontaneously hypertensive rats, and these lower responses were maintained regardless of dexamethasone treatment.